Can psychosocial work conditions protect against age-related cognitive decline? Results from a systematic review. Issue 7 (13th May 2016) - Nexø, Mette Andersen; Meng, Annette; Borg, Vilhelm
Abstract : According to the use it or lose it hypothesis, intellectually stimulating activities postpone age-related cognitive decline. A previous systematic review concluded that a high level of mental work demands and job control protected against cognitive decline. However, it did not distinguish between outcomes that were measured as cognitive function at one point in time or as cognitive decline. Our study aimed to systematically review which psychosocial working conditions were prospectively associated with high levels of cognitive function and/or changes in cognitive function over time. Articles were identified by a systematic literature search (MEDLINE, Web of Science (WOS), PsycNET, Occupational Safety and Health (OSH)). We included only studies with longitudinal designs examining the impact of psychosocial work conditions on outcomes defined as cognitive function or changes in cognitive function. Two independent reviewers compared title-abstract screenings, full-text screenings and quality assessment ratings. Eleven studies were included in the final synthesis and showed that high levels of mental work demands, occupational complexity or job control at one point in time were prospectively associated with higher levels of cognitive function in midlife or late life. However, the evidence to clarify whether these psychosocial factors also affected cognitive decline was insufficient, conflicting or weak. It remains speculative whether job control, job demands or occupational complexity can protect against cognitive decline. Future studies using methodological advancements can reveal whether workers gain more cognitive reserve in midlife and late life than the available evidence currently suggests. The public health implications of a previous review should thereby be redefined accordingly.